The use of radar-rainfall inputs for quantitative precipitation estimation (QPE) in Klang River Basin / Suzana Ramli - Ramli, Suzana (Institute of Graduate Studies, UiTM, 2015)
Flooding is a natural disaster that often occurs in Malaysia due to its heavy rainfall distribution. Lately, the exceptional amount of rainfall worsens the flood situation. Many incidents of floods attributed to the extreme downpour caused massive problems. The capability of gauge to receive data of the torrential precipitation is affected and need to be addressed. Thus, the deployment of radar helps to retrieve better rainfall data due to spatial and temporal factors. Radar has the advantages of detecting rainfall amount with higher resolution and covers larger areas. In addition, radar can also access hilly and ungauged areas with the ability to detect cloud movement and lead to estimation of precipitation. However, radar faces several glitches that hinder its accuracy. Among the problem reported on radar application in quantitative precipitation estimation (QPE) is the inappropriate reflectivity-radar (Z-R) equation used to convert reflectivity to rainfall rate. This research focuses on Z-R relationships in radar conversion to obtain rain data especially for Klang River Basin. In order to integrate radar data into any quantitative precipitation estimation, the suitable Z-R equations must be used to produce acceptable results. Z-R relationship is dependent on rain types and spatial location…